Green communication and networking for Carbon-peaking and Carbon-neutrality: challenges and solutions - Zhisheng NIU; Sheng ZHOU; Yuxuan SUN (Tongxin xuebao)
Driven by the Carbon-peaking and Carbon-neutrality strategic goals, future mobile communication and networks need to drastically reduce energy consumption while satisfying the growing traffic demand.Therefore, it is necessary to study the theories and technologies used to send more information bits with less energy (SMILE).To meet the challenge, it was far from enough to rely solely on the improvements of wireless transmission technologies and hardware.It was necessary to explore efficient energy utilization mechanisms from the perspective of the system and network.Both energy saving and renewable energy utilization approaches were proposed, and solutions for the growing computing energy consumption were provided.Specifically, by introducing hyper-cellular network, agile coverage and elastic access were realized, and thus service base stations and edge servers could enter the sleeping mode to save energy when the traffic volume was low.Meanwhile, by the introduction of renewable energy and the smart adaption of energy flow and information flow, the energy consumption of the power grid could be greatly reduced.Furthermore, green computing and artificial intelligence could be realized through network function virtualization, energy-efficient coordination of communication and compute resources, and distributed computing and coordination approaches of moving agents.